The Antileishmanial Activity of Essential Oils from Some Traditionally Used Medicinal Plants in Iran - Hossein Mahmoudvand; Behrouz Ezatpour; Sareh Jahanbakhsh* (Lorestan University of Medical Sciences, 2016)
Background and Aim: Cutaneous leishmaniasis (CL) is the most common type of leishmaniasis affecting 1.5 million people through the world annually. Treatment of CL by pentavalent antimony compounds remains a challenge because of adverse side effects. The present study was designed to evaluate the in vitro antileishmanial properties of six essential oils from selected spices and herbs ethno-medicinally used in Iran against Leishmania tropica and L. major promastigotes. Materials and Methods: The in vitro antileishmanial effects of selected medicinal plants against L. tropica and L. major promastigotes were evaluated by colorimetric cell viability (MTT) assay. The IC50 values were also calculated by probit test using SPSS software. Results: The findings demonstrated that all the tested essential oils had inhibitory effects on promastigote growth of L. tropica with IC50 values ranging from 3.2µg/mL to 19.3µg/mL and 2.7µg/mL to 18.8µg/mL for L. tropica and L. major, respectively. Zataria multiflora Boiss essential oil significantly (P<0.05) was much more effective than essential oils of the other tested plants and control drugs once they demonstrated lower IC50 values promastigote form. Conclusions: The findings of present study indicated antileishmanial effects of some Iranian medicinal plants particularly Z. multiflora Boiss. However, further studies, on the animal models as well as volunteer human, are needed to confirm these results.